STRATEGI SUKSES BAGI USAHA PEMASARAN JASA - -, Sumaryanto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2009)
ABSTRACT One the marketing strategy of company service can be seen from marketing hotchpotch that is product, price, distribution or place and promotion, but in service marketing mostly in direct correlation to human being make difference to the result of customer satisfaction. For that marketing of service require to pay attention other element like people, physical evidence and process. Service which is either from provider service people will form an evidence physical at customer effect of process giving conducted by service very good. The increasing of service sector triggered by some impeller factor that is: the increasing of consumer demand to quality, reduction is expense of, service activities, internal consumer, product increase and expanding it is organizational nonprofit. Growth Sector service forwards will show growth of significant caused by technological growth of internet, communications and digitalizes so that apart not such a constraint because information and communications can be braided to through mouse click. Keywords: service marketing, service sector, marketing mix, physical evidence